Strategi pengembangan budidaya perairan di Kecamatan Ratahan Timur, Kabupaten Minahasa Tenggara - Wungkana, Lucky; Sinjal, Hengky J.; Pangemanan, Novie P. L.; Lantu, Sartje; Salindeho, Indra R. N.; Wantasen, Adnan S. (Universitas Sam Ratulangi, 2022)
This study aimed to analyze the development of aquaculture and determine aquaculture development strategies that are in accordance with the conditions and potential of the East Ratahan District, Southeast Minahasa Regency. The methodology used was descriptive research method. The research variables observed were the potential and quality of water, land area, and information about the prospects for developing aquaculture. Data collection techniques are observation, interviews, and questionnaires. The results of the aquaculture development analysis using a SWOT analysis showed that the internal factors that influence the development of fish farming in East Ratahan consist of strength factors, namely: district government support, business location and water quality and number of fish culturists. Weakness factors were: Availability of Seeds Inadequate availability of seeds and lack of skilled culturists and lack of working capital. External factors that influenced the development of fish culturists in East Ratahan consist of opportunity factors, namely: high selling value of fish, high market share, and government policies. Threat factors were climate and holticultural crops and illegal fishing. Strategic steps for the development of fish farming businesses in East Ratahan, namely increasing the production capacity of fish aquaculture, improving and maintaining the quality of fish culture products, making agreements between fish culturists in maintaining the safety of aquaculture ponds, optimizing Fish Hatchery Centers, providing skills to fish culturists.